Evaluation of fruit tree waterstress condition and transpiration with heat fl ux sensors - Nagy, A.; Riczu, P.; Tamás, J.; Szabó, Z.; Soltész, M.; Nyéki, J. (International Journal of Horticultural Science, 2016)
In this study the transpiration properties and response to heat stress of Granny Smith and Jonagold apple species were measured. The examinations were set at an orchard near to Debrecen. The chosen trees were two years old, without fruits, in 20l container, placed in the mixture of mulch matrix, wood chips and sawdust and grown at the same climatic conditions. One of the most important goals was to determine the leaf area of the trees which is a basic data for transpiration modeling. Leaf area was larger (signifi cance level p<0.05) in the upper part of the canopy to achieve larger photosynthetic surface. Jonagold species with less leaf number (–18% compared to Granny Smith) reached almost the same canopy area, than Granny Smith, due to larger leaf area of Jonagold. Another aim was to measure the transpiration rate of the apple trees. The transpiration measurements were carried out by sap fl ow meter. Only a small transpiration difference can be found between species. During the investigation time there were wet and cool as well as dry and extremely hot periods. In the case of dry and extreme hot periods the transpiration is decreased, which causes decrease in transpiration and enhanced the water stress of trees.